Pengelolaan Dana Desa Di Masa Pandemi Covid-19 - Irawanto; Riki Welli Saputra; Hefni Hariadi; Moh. Heru Budihantho (stiatabalong.ac.id, 2022)
The purpose of this study is to describe the Management of Village Funds during the COVID-19 pandemic and how it differs from the management of Village Funds before the emergence of the pandemic, which was carried out at the Sinar Baru Village Office, Rantau Badauh District, Barito Kuala Regency. The type of research used is descriptive research. The data and data sources in this are the Sinar Baru Village Government including the Village Head and Village Apparatus, then several community members as well as documents related to research on legislation related to village fund management, APBDes budget data, village profiles, etc. Data collection techniques used are interviews, observation, and documentation. The data analysis techniques used are data reduction, data presentation, conclusions, and data levers. The results showed that the management of Sinar Baru Village funds, Rantau Badauh District, Barito Kuala Regency during the COVID-19 pandemic underwent several changes, which were in the distribution and priority of using village funds in 2020, most of the village funds will be used for handling COVID-19 and assistance. Direct Village Cash (BLT-Dana Desa). Meanwhile, the obstacles faced, for example, were too few unexpected funds/reserve funds/village urgency for handling and preventing COVID-19, so that the Village Government was forced to reshuffle its Village Revenue and Expenditure Budget. Keywords : Covid-19, Pandemic, Village Fund, Village Fund Management, Public Fund Management